APAKAH EKSTENSIFIKASI PAJAK, PEMERIKSAAN PAJAK, DAN SANKSI PAJAK DAPAT MENINGKATKAN PENERIMAAN PAJAK ? - dhiah putri wulandari; Pancawati Hardiningsih (Universitas Sarjanawiyata Tamansiswa, 2022)
The outbreak of the Covid-19 virus has a negative impact on state tax revenue. MSMEs are the sector most affected by the pandemic by declining turnover and income. This study aims to analyze the effect of tax extensification and tax audits on income tax revenues of MSME actors in Semarang City during the Covid-19 pandemic. The research sample consisted of 46 monthly observations for MSME actors in the East Semarang area. The analysis was performed using multiple linear regression analysis. The results showed that tax extensification and tax audits had a positive effect on income tax revenue for MSME actors. Meanwhile, tax sanctions have a negative effect on the income tax receipts of MSME players in Semarang City during the Covid-19 pandemic.